A concepção do professor sobre sua função social: das práticas idealistas à possibilidade de uma ação crítica - Baptista, Maria das Graças de Almeida (2008)
This thesis analyzes the teacher‟s concept about the relation between education and society from the implication of that the way the teacher comprehends this relation determines his/her practice in the learning process. Studies regarding active education in Dewey and Piaget and the proposition of a critic education in Gramsci and Vigotsky indicate that these concepts of education bring to the Brazilian educational system the discussion about the relation between education and society promoting however a rupture in the role the teacher develops in the teaching process. The empirical research, developed through observation, questionnaires and interviews, inquired the concept of ten public school teachers, located in three distinct neighborhoods in the city of João Pessoa Paraíba. The analysis, based on the historical and dialectical references in Gramsci and Vigotsky and the categories built from the theoretical reference and the empirical research, point that the contradictions in the concept of the teacher concerning his/her own pedagogical practice, in the current historical context, disable the establishment of a social project and the construction of an educational concept which benefits the comprehension regarding his/her role in the learning process, at the same time that indicate transformation in the concept and pedagogical practice. This thesis still presents, from analysis of the theoretical concepts approached and the teaching staff concepts, the author‟s contribution in a sense of negation of the inexorability from here and now and the construction of new perspectives to the organization and concept of a critical pedagogical practice. Therefore, it proposes further investigations in the sense of deepening the studies developed about the relation between learning and development and the theoretical and practical concepts from future teachers.